A brief from the leaf: latest research to inform our understanding of the phyllosphere microbiome. (June 2019) - Leveau, Johan HJ
Abstract : The plant leaf surface, or phyllosphere, represents a unique and challenging microbial biome with a diverse and dynamic community of commensal, parasitic, and mutualistic agents of microscopic proportions. This mini-review offers a digest of recently published research dedicated to the study of phyllosphere microbiota, framed in the context of processes and outcomes of microbial community assembly, structure, and (inter)activity in the phyllosphere, with particular focus on the contributions of environment, plant, and microbe, and on the potential benefits of interrogating those contributions at finer resolutions.